2003
DOI: 10.1159/000072859
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic mouse models for myotonic dystrophy type 1 (DM1)

Abstract: The study of animal models for myotonic dystrophy type 1 (DM1) has helped us to ‘de- and reconstruct’ our ideas on how the highly variable multisystemic constellation of disease features can be caused by only one type of event, i.e., the expansion of a perfect (CTG)n repeat in the DM1 locus on 19q. Evidence is now accumulating that cell type, cell state and species dependent activities of the DNA replication/repair/recombination machinery contribute to the intergenerational and somatic behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 129 publications
0
23
0
Order By: Relevance
“…The myotonic dystrophies (DM1 and DM2) are characterized by nuclear RNA aggregates formed by CUG or CCUG repeat expansions in the 3′ UTR of DMPK and 5′UTR of SIX5 (DM1) and in the first intron of ZNF9 (DM2) (Wansink and Wieringa 2003). CUG-binding protein and muscleblind-like protein 1 can bind these RNA repeats and are involved in alternative splice site selection.…”
Section: Discussionmentioning
confidence: 99%
“…The myotonic dystrophies (DM1 and DM2) are characterized by nuclear RNA aggregates formed by CUG or CCUG repeat expansions in the 3′ UTR of DMPK and 5′UTR of SIX5 (DM1) and in the first intron of ZNF9 (DM2) (Wansink and Wieringa 2003). CUG-binding protein and muscleblind-like protein 1 can bind these RNA repeats and are involved in alternative splice site selection.…”
Section: Discussionmentioning
confidence: 99%
“…This would place DM1 into the large category of alternative splicing disorders (reviewed in references 13 and 38). Previously, already strong evidence was provided that a different mechanism, involving titration of RNA processing factors by the abnormal long expanded (CUG) n repeats in the 3Ј-UTR of DMPK mRNA, has transeffects on the processing of other transcripts, like that of the chloride channel, tau protein, and insulin receptor in patients with DM1 (53).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that expansion of the (CTG) n repeat results in reduced appearance of DMPK in the cytoplasm (53). Studies in knockout mouse and myocyte cell models indicated that lack of DMPK protein may be associated with typical DM1 symptoms like myopathy and heart conduction defects, perhaps via effects on Ca 2ϩ or Na ϩ ion homeostasis (5,6,25,35,42).…”
mentioning
confidence: 99%
“…3 In myotonic dystrophy, CUG-containing RNA transcripts are improperly spliced and exported out of the nucleus, affecting the function of both the DM1 gene and other RNA transcripts dependent on CUG-interacting proteins for proper splicing and translation. 7,8 The mechanism of trinucleotide repeat expansion is of considerable interest not only for a general understanding of genome stability but also because the timing and degree of expansion influences disease pathology and timing of disease onset. The repeats can expand during passage from one generation to the next as well as in somatic cells.…”
Section: Abbreviationsmentioning
confidence: 99%
“…9,10 In addition, somatic instability is observed in the affected tissues of the various diseases, for example striatal neurons in HD and muscle cells of DM, and is recapitulated in mouse models. 8,11,12 Somatic instability may be a contributing factor in determining the timing of disease onset.…”
Section: Abbreviationsmentioning
confidence: 99%